The mandibular muscles of the Puma concolor (Mammalia, Carnivora, Felidae) (2016)
This manuscript describes the mandibular muscles of the puma (Puma concolor), a widely sparse American carnivorous mammal. The muscles on the right and left side of the head of three specimens- two adult males and one young female - were dissected and photographed. This study increases our knowledge on the mandibular soft tissue and adds important anatomical information to the poorly known and documented musculature of this felid, the largest of the subfamily Felinae.